2014
DOI: 10.1063/1.4896677
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation-induced grain growth in nanocrystalline reduced activation ferrite/martensite steel

Abstract: In this work, we investigate the microstructure evolution of surface-nanocrystallized reduced activation ferrite/martensite steels upon high-dose helium ion irradiation (24.3 dpa). We report a significant irradiation-induced grain growth in the irradiated buried layer at a depth of 300–500 nm, rather than at the peak damage region (at a depth of ∼840 nm). This phenomenon can be explained by the thermal spike model: minimization of the grain boundary (GB) curvature resulting from atomic diffusion in the cascade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In experiment, a significant grain growth due to irradiation was observed in nanocrystalline RAFM steels [54]. It has also been shown that He atoms aggregate in defects (point defect, grain boundary) to form bubbles in structural materials that result in void swelling and embrittlement [13,55,56].…”
Section: Vacancy Trapping For Multiple He In Presence Of Cr and Wmentioning
confidence: 96%
“…In experiment, a significant grain growth due to irradiation was observed in nanocrystalline RAFM steels [54]. It has also been shown that He atoms aggregate in defects (point defect, grain boundary) to form bubbles in structural materials that result in void swelling and embrittlement [13,55,56].…”
Section: Vacancy Trapping For Multiple He In Presence Of Cr and Wmentioning
confidence: 96%
“…The incoherent shaped structures which are randomly distributed all over the surface have been transformed into granular morphology with distinct grain boundaries. Similar kind of structures by ion implantation on different metals have been reported previously by Mallick et al, Kaoumi et 31,33,34 The grain morphology is explained on the basis of thermal spike model. 33,34 The ion induced thermal spikes and their size play a central role in grain morphological process.…”
Section: B Surface Morphology Of Brass Substratesmentioning
confidence: 51%
“…Similar kind of structures by ion implantation on different metals have been reported previously by Mallick et al, Kaoumi et 31,33,34 The grain morphology is explained on the basis of thermal spike model. 33,34 The ion induced thermal spikes and their size play a central role in grain morphological process. At increased in dose, temperature of surface and impacts of thermal spike also increase significantly.…”
Section: B Surface Morphology Of Brass Substratesmentioning
confidence: 51%
See 1 more Smart Citation
“…In addition, the increase of average grain size from 40 nm to 60 nm was observed in the NS austenite steel SW316SS after irradiated with Fe ions [74]. Irradiation induced grain growth was also reported in NS ferrite/martensite steel produced by surface mechanical attrition treatment (SMAT) [75]. Moreover, irradiation induced grain growth has also been widely observed in nanocrystalline thin films (for example, Zr NS film [76], Fe/Fe (Zr) NS films [77], Ni film [78], Pd film [79], Zr-Fe NS film [80] and Zr, Pt, Cu, and Au NS films [81]).…”
Section: Irradiation Resistance Of Ns Materialsmentioning
confidence: 99%